A new species of Neorhynchoplax (Crustacea: Decapoda: Brachyura: Hymenosomatidae) from Taiwan - Hsueh, Pan-Wen (Zootaxa, 2018)
A new hymenosomatid crab, Neorhynchoplax chipolini sp. nov., is described from Taiwan. Of the 32 known species of Neorhynchoplax, only five other species possess a posterolateral tooth on the carapace and unarmed ambulatory dactyli as in N. chipolini sp. nov.: i.e. N. attenuipes (Chopra & Das, 1930), N. falcifera Naruse, Mendoza & Ng, 2008, N. sinensis (Shen, 1932), N. tuberculata (Chopra & Das, 1930), and N. venusta Ng, 2015. Neorhynchoplax chipolini sp. nov., however, differs from these congeners by having the median rostral tooth distinctly bent downwards and the presence of a tubercle on the inner anterolateral margin of the first exopod article of the third maxilliped. Brood size, egg diameters, and the protective structure of eggs in N. chipolini sp. nov. are noted. A table for the habitat preferences of all known species of Neorhynchoplax is provided.